Father’s involvement in Portuguese families: Fathers’ and mothers’ beliefs about the role of the father - Santos, C.; Monteiro, L.; Torres, N.; Salinas-Quiroz, F.; Neves, A.; Amaral, R. (26th ISSBD Biennial Meeting of the International Society for the Study of Behavioural Development (Conference canceled), 2020)
During the last decades the Portuguese society has undergone vast changes with the majority of the families (with small children) having both parents employed. As a response new employment and family policies have been developed attempting to promote gender equality, both in the family and in the workplace (Wall et al., 2016). The main goal of this study was to analyze predictors of father involvement with the child in different domains of daily life (e.g., Care, Play, Teaching and Discipline). Child’s age and sex, as well as parents’ age, education, working hours and their beliefs about the role of the father were considered. We aimed to understand if father’s involvement is explained by his own beliefs about the role of the father, or if it is regulated by maternal beliefs, considered in this study as a potential gatekeeping mechanism (McBride et al., 2005). 234 nuclear Portuguese families with preschool age children participated. Mothers and fathers independently completed the Parental Involvement scale (Monteiro et al., 2008), and the What Is a Father? Questionnaire (WIAF; Schoppe, 2001). Results show that the total variance explained by the three predictor blocks (sociodemographic, beliefs about the role of the father, interaction between beliefs and child’s sex) reached statistical significance for direct care (F(13,240)= 2.44; p= .006, ? R2 = .14), but not for Play or Teaching and Discipline. For Direct Care, Mother's Nontraditional Beliefs was a Significant Predictor (b= .25, p< .01), and a significant interaction between her beliefs and the child’s sex was found (b= -.20, p< .01), with the effect been higher for girls than for boys. For Teaching/Discipline only parent's education (b= .25, p< .01) has a significant effect. The results will be discussed in the context of the different beliefs and roles caregivers have in the child's life.